Levobupivacaine induces vasodilatation, but not vasoconstriction, in rat mesenteric artery - Liciane dos Santos MENEZES; Liane Maciel de Almeida SOUZA; Márcio Roberto Viana dos SANTOS; Patrícia Santos Cunha MENDONÇA; Ítalo José Alves MOREIRA; Allan Carlos Araújo de OLIVEIRA
Abstract Introduction Levobupivacaine (LEVO) can replace analgesia because it exhibits low toxicity and causes minor vasoconstriction, enabling its use in patients in whom vasoconstrictors are contraindicated. Objective We aimed to evaluate the effects of LEVO in isolated rat superior mesenteric artery by using the vascular reactivity technique and compare its effect to that of lidocaine. Material and method Arterial rings were obtained from the mesenteric artery of male Wistar rats and kept in organ baths. For recording isometric contractions, each ring was suspended by cotton threads from a force transducer, which was connected to a data acquisition system. Result Both lidocaine and LEVO did not show a vasoconstrictor effect on the basal tone of the arterial rings with functional endothelium. However, when the rings were pre-contracted with phenylephrine, both drugs were able to induce concentration-dependent vasodilatation. The vasodilator effect induced by LEVO did not change after removal of the endothelium, or with the addition of tetraethylammonium (1 mM), a non-selective K+ channel blocker. In the rings without functional endothelium, which were pre-contracted with depolarizing Tyrode's solution (KCl 80 mM), LEVO-induced vasodilatation was not significantly different from that observed in the rings pre-contracted with phenylephrine. Moreover, it did not show a significant additional vasodilator effect compared to the maximal vasodilator effect of nifedipine. Conclusion This study demonstrated that LEVO produces a vasodilator effect in the rat superior mesenteric artery in an endothelium-independent manner. This effect seems to be mediated via Ca2+ channel blockade in the vascular smooth muscle cells.